Pentingnya pembentukan kebiasaan menabung sejak dini untuk mempersiapkan masa depan siswa TK - Juwono, Angela; Widjaja, Audrey Cerelia; Linawati, Nanik (Penamas: Journal of Community Service, 2024)
Financial problems often come unexpectedly. Applying adequate financial management is the primary key to facing future financial challenges. Therefore, sufficient knowledge is needed to build proper habits for managing money. Community service activities provided to TK Petra 9 Surabaya students involved three kindergarten classes, each consisting of 22 to 23 students. This program aims to introduce proper money management habits early on as a preparation for a stable future financial condition. In its implementation, the method used is service learning, which can directly cultivate awareness of problem-solving. The application of this method included watching puppet shows, coloring pictures of professions, ice-breaking, and making piggy banks. Puppet show activities positively influence students' character development, while coloring and making piggy banks help sharpen children's motor skills. Therefore, community service activity has been proven to have a constructive impact on the early childhood development of good habits.